2008
DOI: 10.1007/s10340-008-0224-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance of two Trichogramma brassicae strains under greenhouse and field conditions for biocontrol of the silver Y moth in spinach cultures

Abstract: The suitability of Trichogramma brassicae Bezd. (Hymenoptera: Trichogrammatidae) to control the silver Y moth, Autographa gamma (L.) (Lepidoptera: Noctuidae) in spinach was investigated under greenhouse and Weld conditions. Two strains of T. brassicae were selected to study host searching eYciency and dispersal ability of the wasps on spinach. The experiments were conducted with deWned release densities. The results show that T. brassicae strain I failed to locate host eggs in all experiments. In contrast, T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…For example, an Italian strain of T. brassicae Bezdenko is more efficient in controlling Ostrinia nubilalis Hübner in Spain than the French strain (Eizaguirre et al 1998). Klug and Meyhöfer (2009) described similar findings when comparing performance of two strains of T. brassicae in locating eggs of the silver Y moth (Autographa gamma Linnaeus). However, this is not always the case in host-parasitoid systems (Vos and Vet 2004) and our results showed that strains of T. evanescens did not differ in their parasitism level.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…For example, an Italian strain of T. brassicae Bezdenko is more efficient in controlling Ostrinia nubilalis Hübner in Spain than the French strain (Eizaguirre et al 1998). Klug and Meyhöfer (2009) described similar findings when comparing performance of two strains of T. brassicae in locating eggs of the silver Y moth (Autographa gamma Linnaeus). However, this is not always the case in host-parasitoid systems (Vos and Vet 2004) and our results showed that strains of T. evanescens did not differ in their parasitism level.…”
Section: Discussionsupporting
confidence: 69%
“…1) which displayed higher level of parasitism in the laboratory showed a lower walking activity in the greenhouse than during the laboratory trials (Gonsard, personal communication). In addition, the dispersal capacities of Trichogramma often vary between strains, which may ultimately impact their effectiveness in attacking hosts (Klug and Meyhöfer 2009) and notably between the strains tested in our study (E. Tabone, unpublished data). Similarly, the horizontal and vertical searching activities of Trichogramma may also affect parasitism efficiency (El-Wakeil et al 2008).…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, parasitoid effectiveness varies largely according to species (and even strains of one species) (Klug and Meyhöfer 2009;Tabone et al 2010) or climatic conditions (Smith 1996). Abiotic factors can affect multiple biological traits of these parasitoids (Scott et al 1997;Pratissoli et al 2005;Oliveira et al 2007;Bueno et al 2008), and temperature, in particular, influences development rate, parasitism rate, sex ratio and longevity (Hoffmann and Hewa-Kapuge 2000;Pizzol et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Parasitoid effectiveness sometimes varies according to strains (Pizzol and Wajnberg 1994;Klug and Meyhöfer 2009;Tabone et al 2010) or climatic conditions (Smith 1996). Among Trichogramma species, Trichogramma cacoeciae Marchal is largely used as biological control agent against various pests and is a species spread worldwide (Pintureau 1997).…”
Section: Introductionmentioning
confidence: 99%